Changes in Indicators of Special Physical Preparedness in Badminton Players Aged 10–11 under the Influence of Specially Selected Exercises - Shevchenko, Oleg; Mulyk, Kateryna; Paievskyi, Volodymyr; Skaliy, Aleksander; Guba, Anatolii; Skaliy, Tetiana; Anosova, Olena (Physical Education Theory and Methodology, 2023)
Study purpose. The study purpose was to determine changes in indicators of special physical preparedness and speed of attacking strokes in badminton players aged 10–11 under the influence of specially selected exercises. Materials and methods. The study participants were young badminton players aged 10–11 (12 boys), whose sports experience was 2-3 years. The study lasted 3 months and included: testing of special physical preparedness and assessment and analysis of the speed of attacking attacking strokes of young badminton players. Results. Analysis of the results of the study showed positive changes in the results of special physical preparedness, accuracy and speed of attacking strokes. The complex development of the speed-strength abilities of young badminton players was determined by the exercises of throwing a ball weighing 1 kg, triple long jump and jumping rope. This was manifested in the execution of attacking strokes from the place and in jumping and moving, but there was a significant increase in results in the triple jump and jumping rope. The development of speed endurance determined the 4-point center-to-center movement exercise, but the results did not change significantly over the course of the study. Accuracy indicators of attacking strokes significantly increased by an average of 2,58%. The results of the speed of attacking strokes also had a significant increase by an average of 29.41%. The use of complexes for training the accuracy of attacking strokes along with targets with a gradual complication of exercises increased the results of test exercises for accuracy and speed of execution. The indicators of the speed of attacking strokes on the left and on the right correlate with each other. The accuracy results of the right hand strokes along the line significantly correlate with right hand strokes along the diagonal and the triple long jump from a place. This indicates the connection of speed-strength abilities with the performance of attacking strokes by young badminton players. Indicators of a triple long jump from a place, jumping rope for 1 min. and throwing a ball weighing 1 kg are significantly correlated with each other, which indicates the complex development of the speed-strength abilities of young badminton players. Conclusions. The presented complexes of special preparatory exercises had a positive effect on changes in the indicators of special physical preparedness, accuracy and speed of the attacking strokes, which makes it possible to recommend them to 10–11-year-old badminton players in the training process.